Guidance for Portability of Australian Microcredentials. (Universities Australia, 2021)
The Deputy Vice-Chancellors (Academic) have developed recommended guidance to assist in portability of microcredentials. The guidance recommends three principle-based standards that allow universities to accurately determine the extent of learning that a microcredential attests, and is a statement reflecting those issues on which a reasonable understanding of consensus exists. The standards state that microcredentials are quality assured and verifiable, with sufficient, relevant metadata; microcredentials have an understandable unit of exchange, and microcredentials have clear evidence of achievement or learning outcome. The guidance is intended to help others who may wish to develop credentials that can be easily recognised by a university. [Publisher summary, ed]